PELAKSANAAN PEMBELAJARAN KEWIRAUSAHAAN KELAS XII DI SLB NEGERI A KOTA BANDUNG - Sadiqin, _ (2017)
This research entitled "Implementation of Class XII Entrepreneurship Learning In SLB Negeri A Bandung city. The problem discussed in this research is how the plan, implementation, obstacles, efforts and evaluation of entrepreneurial learning for students with visual impairment in SLBN A Bandung city. The objective to be achieved from this research process is to know the description of the entrepreneurship applied to blind students in SLBN A Bandung city. The approach used is qualitative and described narratively, to reveal the implementation of class XII entrepreneurship learning in SLBN A Bandung city. Data collection techniques in this research are interview, observation and documentation study. The results of research on the implementation of entrepreneurial learning in students with visual impairment is the learning plan for students there is no special requirement to follow the learning and RRP used following the curriculum 2013. Implementation of entrepreneurial learning with the given material is cultivating catfish, sate maranggi and compost processing. The obstacles in the implementation of learning is the lack of learning resources and learning media that can be used as a support in teaching and learning activities. Efforts to overcome these obstacles by varying media and learning resources that can support the learning and teaching process. Entrepreneurship learning is one of the capital for students in running life in society. The implications of teachers should be more attention to the uniqueness of students, and they can also be used as a reference in determining the needs so that it can create a special learning program in order to develop all the potential that is still owned by students. ----- Penelitian ini berjudul "Pelaksanaan Pembelajaran Kewirausahaan Kelas XII Di SLB Negeri A Kota Bandung. Masalah yang di bahas dalam penelitian ini adalah bagaimana rencana, pelaksanaan, hambatan, upaya dan evaluasi pembelajaran kewirausahaan bagi siswa tunanetra di SLBN A Kota Bandung. Tujuan yang ingi dicapai dari proses penelitian ini adalah mengetahui gambaran tentang kewirausahan yang diterapkan pada siswa tunanetra di SLBN A Kota Bandung. Pendekatan yang digunakan adalah kualitatif dan dideskripsikan secara naratif, untuk mengungkap pelaksanaan pembelajaran kewirausahaan kelas XII di SLBN A Kota Bandung. Teknik pengumpulan data dalam penelitian ini yaitu wawancara, observasi dan studi dokumentasi. Hasil penelitian tentang pelaksanaan pembelajaran kewirausahaan pada siswa tunanetra yaitu rencana pembelajaran bagi siswa tidak ada persyaratan khusus untuk mengikuti pembelajaran tersebut dan RRP yang digunakan mengikuti kurikulum 2013. Pelaksanaan pembelajaran kewirausahaan dengan materi yang diberikan yaitu membudidayakan ikan lele, sate maranggi dan pengolahan pupuk kompos. Adapun hambatan dalam pelaksanaan pembelajaran adalah kurangnya sumber belajar dan media pembelajaran yang dapat digunakan sebagai penunjang dalam kegiatan belajar mengajar. Upaya mengatasi hambatan tersebut dengan cara memvariasikan media dan sumber belajar yang bisa menunjang proses belajar dan mengajar. Pembelajaran kewirausahaan merupakan salah satu modal bagi siswa dalam menjalankan kehidupan di masyarakat. Implikasi sebaiknya guru lebih perhatian terhadap keunikan siswa, dan mereka juga bisa dijadikan acuan dalam menentukan kebutuhan sehingga bisa membuat sebuah program pembelajaran secara khusus guna mengembangkan segala potensi yang masih dimiliki oleh siswa.